Drying Performance of Rotating and Solar Tunnel Dryer for Production of Quality Dried Fish (Progressive Agriculture, 2013)
Studies were conducted to evaluate the drying performance of rotating and solar tunnel dryer for the production of high quality dried fish products. Three marine fish species : Silver jew fish (Johnius argentatus), Bombay duck (Harpodon nehereus) and Ribbon fish (Trichiurus haumela) were used for drying in a rotating dryer and solar tunnel dryer. Temperature and relative humidity were measured at time interval during the whole drying period. During 20 hours of drying in rotating dryer, temperature and humidity varied from 15-20oC and 45 to 72%, respectively. On the other hand, air temperature outside the tunnel dryer varied from 28 to 32.83oC. Temperature inside the tunnel dryer varied from 31.33oC at 3.00 pm to 47.78oC at 12.00 pm. Humidity outside the tunnel dryer ranged from 58.83 to 74% and inside from 33.83% to 68% showing an inverse relationship between temperature and humidity. Moisture content of the fresh Ribbon fish, Silver Jew fish and Bombay duck was in the range of 78.7% to 85.47% with highest value was found in Bombay duck and lowest value in Ribbon fish. After 31 hours of drying in solar tunnel dryer, moisture content decreased in the range of 14.05 to 16.19%. whereas, after 20 hours of drying in rotating dryer final moisture content reached in the range of 16.36 to 19.1%. The present study indicated that drying performance of rotating dryer with low humidity was faster than that of solar tunnel dryer producing quality dried products.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16869 Progress. Agric. 20(1 & 2): 173 181, 2009